Standardization of production of mycoherbicidal agent Colletotrichum dematium FGCC# 20 by solid substrate fermentation - A.K. PANDEY, JAYA SINGH and (Indian Phytopathology, 2009)
The aim of the present study is to select a suitable, cheaper and easily available agro-waste substrate for mass production of mycoherbicidal agent Colletotrichum dematium FGCC# 20, which is a highly effective bioherbicidal agent against Parthenium hysterophorous. The outcome of the study indicates that, pretreated sugarcane bagasse supported maximum mycelia coverage while maize cob grits supported maximum sporulation and cause maximum seedling mortality.